Guidelines 2021 - Novelties in the protocol of advanced life support - nikolovski, srdjan (Journal Resuscitatio Balcanica, 2021)
Adult advanced life support guidelines 2021 provided by the European Resuscitation Council in its largest extent do not differ signifficantly from equivalent guidelines published six years ago. However, some important points were further emphasized, and some protocols show new additions and structural changes.According to the new guidelines, there is a greater recognition that patients with both in-hospital and out-of-hospital cardiac arrest have premonitory signs, and that many of these arrests may be preventable. High-quality chest compressions with minimal interruption, early defibrillation, and treatment of reversible causes remained high priority steps in resuscitation process. New guidelines also recommend that, if an advanced airway is required, rescuers with a high tracheal intubation success rate should use this technique.With regard to using diagnostic procedures, medications, and special methods of cardiopulmonary resuscitation, newest guidelines also made new suggestions. According to these guidelines, when adrenaline is used, it should be used as soon as possible when the cardiac arrest rhythm is non-shockable, and after three defibrillation attempts for a shockable cardiac arrest rhythm. The guidelines recognise the increasing role of point-of-care ultrasound in peri-arrest care for diagnosis, but emphasise that it requires a skilled operator, and the need to minimise interruptions during chest compression. Additionally, 2015 guidelines suggested use of point-of-care ultrasound in diagnosing several various conditions with potential of causing cardiac arrest. However, 2021 guidelines limited indications in diagnosing only cardiac causes, such as tamponade or pneumothorax.The guidelines also reflect the increasing evidence for extracorporeal cardiopulmonary resuscitation as a rescue therapy for selected patients with cardiac arrest when conventional advanced life support measures are failing or to facilitate specific interventions.Additionally, newest guidelines made significant changes in the order of steps used in the In/hospital resuscitation algorithm, as well as changes in several very important steps of treating tachycardias and high heart rate accosiated arrhythmias.
Keywords: Advanced Life Support; Guidelines 2021; Outhospital cardiac arrest; In- hospital cardiac Arrest